Development and optimization of smart raft forming in-situ gel for gastroretentive drug delivery of anthelmintic drug - Dhawal Dorwal. Ravikant Gupta (South Eastern European Journal of Public Health, 2025)
The main objective of the research was to formulate an oral raft-forming in situ gelling system of Albendazole (ABZ) to improve gastric retention and drug release in a controlled manner and remain floating in the stomach for a prolonged time. In this study in situ gelling system was developed and optimized by a two-factor at three-level (32) factorial design. It was analyzed to study the impact of two independent variables viz sodium alginate [A] and HPMC K4M [B] on the responses, such as floating lag time, percentage (%) water uptake at 2 h, and % drug release at 6 h and 12 h. An in vitro gelation study of the in situ gel formulation showed immediate gelation and was retained for a longer period. From the obtained results of 32 factorial designs, it was observed that all the selected factors had a significant effect on the chosen response, supporting the precision of design employed for optimization. Thus, the developed oral raft-forming in situ gelling system of ABZ can be a promising and alternate approach to enhance retention in the stomach and to attain sustained release of drug by floating, thereby augmenting the therapeutic efficacy of ABZ.